Influence of Lactobacillus kefiri on Intestinal Microbiota and Fecal IgA Content of Healthy Dogs - Gaspardo, Alba; Zannoni, Augusta; Turroni, Silvia; Barone, Monica; Sabetti, Maria Chiara; Zanoni, Renato Giulio; Forni, Monica; Brigidi, Patrizia; Pietra, Marco (Frontiers in Veterinary Science, 2020)
The increasing incidence of gastrointestinal tract pathologies in dogs and the worrisome topic of antibiotic resistance have raised the need to look for new therapeutic frontiers. Of these, the use of probiotics represents a potential therapeutic alternative. Lactobacillus kefiri (Lk) is a species of Lactobacillus isolated from kefir. Previous studies have demonstrated that its administration in mice downregulates the expression of proinflammatory mediators and increases anti-inflammatory molecules in the gut immune system. It also regulates intestinal homeostasis, incrementing immunoglobulin A (IgA) secretion. Since Lk has never been studied as a single probiotic in dogs, the aim of this study was to evaluate the safety of Lk in dogs, and its effect on IgA secretion and on intestinal microbiota composition. Ten healthy dogs without a history of gastrointestinal diseases were included. The dogs received Lk at a dose of 107 live microorganisms orally, once daily for 30 days. The fecal samples were tested before administration, in the middle, at the end and 30 days after discontinuation. The IgA secretion concentration and microbiota composition were evaluated on the fecal samples. The results in this study suggested that Lk did not influence the concentration of IgA, nor significant changes of the intestinal microbiota were observed during and after the treatment. Therefore, additional studies, are needed to investigate if an higher daily dosage of Lk can influence the intestinal homeostasis of dogs.